What Are the Complications of Allograft Reconstructions for Sarcoma Resection in Children Younger Than 10 Years at Long-term Followup?. Issue 3 (March 2018) - Aponte-Tinao, Luis A.; Albergo, Jose I.; Ayerza, Miguel A.; Muscolo, D. Luis; Ing, Federico Milano; Farfalli, German L.
Abstract: Background: Preservation of limb function after resection of malignant bone tumors in skeletally immature children is challenging. Resection of bone sarcomas and reconstruction with an allograft in patients younger than 10 years old is one reconstructive alternative. However, long-term studies analyzing late complications and limb length discrepancy at skeletal maturity are scarce; this information would be important, because growth potential is altered in these patients owing to the loss of one physis during tumor resection. Questions/purposes: At a minimum followup of 10 years after reconstructions in children younger than 10 years of age at the time of reconstruction, we asked what is (1) the limb length discrepancy at skeletal maturity and how was it managed; (2) the risk of amputation; (3) the risk of allograft removal; and (4) the risk of second surgery resulting from complications? Methods: Between 1994 and 2006, we performed 22 bone allografts after bone sarcoma resections in children younger than 10 years of age. Of those, none were lost to followup before the minimum followup of 10 years was reached, and an additional six had died of disease (of whom three died since our last report on this group of patients), leaving 16 patients whom we studied here. Followup on these patients was at a mean of 13.5 years (range, 10-22 years). During the period in question, no other treatments (such as extendible prostheses, amputations, etc) were used. The mean age at the time of the original surgery was 7 years (range, 2–10 years), and the mean age of the 16 alive patients at last followup was 20 years (range, 15–28 years). This series included 10 boys and six girls with 14 osteosarcomas and two Ewing sarcomas. Ten reconstructions were performed with an intercalary allograft and six with an osteoarticular allograft. The growth plate was uninvolved in three patients, whereas in the remaining 13, the growth plate was included in the resection (seven intercalary and six osteoarticular allografts). Limb length discrepancy at skeletal maturity was measured with full-length standing radiographs, and data were collected by retrospective study of a longitudinally maintained institutional database. The risk of amputation, allograft removal, and secondary surgery resulting from a complication was calculated by a competing-risk analysis method. Results: We observed no limb length discrepancy at skeletal maturity in the three patients with intercalary resections in whom we preserved the physes on both sides of the joint (two femurs and one tibia); however, one patient developed malalignment that was treated with corrective osteotomy of the tibia. The remaining 13 patients developed limb length discrepancy as a result of loss of one physis. Seven patients (four femurs, two tibias, and one humerus) developed shortening of ⩽ 3 cm (mean, 2.4 cm; range, 1–3 cm) and no lengthening was performed. Six patients developed > 3 cm of limb discrepancy at skeletal maturity (all distal femoral reconstructions). In four patients this was treated with femoral lengthening, whereas two declined this procedure (each with 6 cm of shortening). In the four patients who had a lengthening procedure, one patient had a final discrepancy of 4 cm, whereas the other three had equal limb lengths at followup. The risk of amputation was 4% (95% confidence interval [CI], 0-15) and none occurred since our previous report. The risk of allograft removal was 15% (95% CI, 1-29) and none occurred since our previous report on this group of patients. The risk of other operations resulting from a complication was 38% (95% CI, 19-57). Eleven patients underwent a second operation resulting from a complication (three local recurrences, five fractures, one infection, one nonunion, and one tibial deformity), of which three were performed since our last report on this group of patients. Conclusions: Limb length inequalities and subsequent procedures to correct them were common in this small series of very young patients as were complications resulting in operative procedures, but overall most allografts remained in place at long-term followup. In skeletally immature children, bone allograft is one alternative among several that are available (such as rotationplasty and endoprosthesis), and future studies with long followup may be able to compare the available options with one another. Level of Evidence: Level IV, therapeutic study.